2021
DOI: 10.3389/fonc.2021.774088
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Heterogeneity and Immune Response Indicators to Predict Overall Survival in a Retrospective Study of HER2-Borderline (IHC 2+) Breast Cancer Patients

Abstract: Breast cancer (BC) categorized as human epidermal growth factor receptor 2 (HER2) borderline [2+ by immunohistochemistry (IHC 2+)] presents challenges for the testing, frequently obscured by intratumoral heterogeneity (ITH). This leads to difficulties in therapy decisions. We aimed to establish prognostic models of overall survival (OS) of these patients, which take into account spatial aspects of ITH and tumor microenvironment by using hexagonal tiling analytics of digital image analysis (DIA). In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 116 publications
1
7
0
Order By: Relevance
“…Previous studies (38,39,43,44) As in previous studies including Ki67, PR, and HER2 IHC (38, 43, 44), we found a non-linear association between the rate of Ki67 and its entropy: high ITH values are detected only in the middle of the range of the biomarker expression rate, while lower ITH is characteristic at the low and high ends of the range (Fig. 4).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies (38,39,43,44) As in previous studies including Ki67, PR, and HER2 IHC (38, 43, 44), we found a non-linear association between the rate of Ki67 and its entropy: high ITH values are detected only in the middle of the range of the biomarker expression rate, while lower ITH is characteristic at the low and high ends of the range (Fig. 4).…”
Section: Discussionsupporting
confidence: 80%
“…AshD) was calculated for the intratumoral distributions of ER, PR, Ki67, and HER2 positive cells across the grid as described in(38,39,43,44). SAS Institute Inc., Cary, North Carolina, USA) and R (version 4.1.0) were used for statistical analyses and to generate plots.…”
mentioning
confidence: 99%
“…Intratumoral staining heterogeneity is well known, with three patterns (mosaic, scattered, and clustered) being described 49 . Intratumoral heterogeneity is acknowledged as a source of disconcordance within HER2 IHC scoring 50–52 and has been investigated as a separate negative prognostic marker 53–57 . Incomplete fixation has been recognised as one cause of immunoreactivity heterogeneity 54 .…”
Section: Discussionmentioning
confidence: 99%
“…49 Intratumoral heterogeneity is acknowledged as a source of disconcordance within HER2 IHC scoring [50][51][52] and has been investigated as a separate negative prognostic marker. [53][54][55][56][57] Incomplete fixation has been recognised as one cause of immunoreactivity heterogeneity. 54 The pitfall of HER2 heterogeneity in the evaluation of HER2-low can be accounted for in the development of the software.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, changes in therapy are made according to imaging size-based response assessment, RECIST 1.1 (response evaluation criteria in solid tumors), and on follow-up CT examinations [16,17]. Interpretations of most malignant tumors with heterogenous growth and response patterns remains an issue of clinical decision, especially because of the limitations of RECIST 1.1 [18][19][20][21]. Intra-tumoral heterogeneity and tumor infiltration are newer imaging features that can be spatially assessed on imaging using quantitative measures of image signal heterogeneity and may improve prognostication compared with size assessment alone [22,23].…”
Section: Introductionmentioning
confidence: 99%